Spaces with compact-countable weak-bases - Li, Zhaowen; Li, Quingguo (Scientia Series A: Mathematical Sciences, 2025)
In this paper, we establish the relationships between spaces with a compact-countable weak-base and spaces with various compact-countable networks, and give two mapping theorems on spaces with compact-countable weakbases.
Keywords: weak-bases; \(sn\)-networks; \(cs\)-networks; \(k\)-networks; \(k-spaces\); \(α_4\)-spaces